The Binding Properties and Physiological Functions of Recoverin - Zang, Jingjing; Neuhauss, Stephan C. F. (Frontiers in Molecular Neuroscience, 2018)
Recoverin (Rcv) is a low molecular-weight, neuronal calcium sensor primarily located in photoreceptor outer segments of the vertebrate retina. Ca2+-bound Rcv has been proposed to inhibit G-protein-coupled receptor kinase (GRK) in darkness. During the light response, the Ca2+-free Rcv releases GRK, which in turn phosphorylates visual pigment, ultimately leading to the cessation of the visual transduction cascade. Technological advances over the last decade have contributed significantly to a deeper understanding of Rcv function. These include both biophysical and biochemical approaches that will be discussed in this review article. Furthermore, electrophysiological experiments uncovered addition functions of Rcv, such as regulation of the lifetime of Phosphodiesterase-Transducin complex. Recently, attention has been drawn to different roles in rod and cone photoreceptors. This review focuses on Rcv binding properties to Ca2+, disc membrane and GRK, and its physiological functions in phototransduction decay and during light adaptation.